Unexpectedly high prevalence of rare genetic disorders in kidney transplant recipients with an unknown causal nephropathy. (18th July 2014) - Quaglia, Marco; Musetti, Claudio; Ghiggeri, Gian Marco; Fogazzi, Giovanni Battista; Settanni, Fabio; Boldorini, Renzo Luciano; Lazzarich, Elisa; Airoldi, Andrea; Izzo, Cristina; Giordano, Mara; Stratta, Piero
Abstract Background Patients with a rare genetic disease may receive renal transplantation (KTx) without a correct diagnosis of causal nephropathy and therefore develop unexpected and even severe complications. The aim of the study was to describe the cases of rare genetic disorders diagnosed after KTx, in order to draw clinical lessons for the transplant physician. Methods We retrospectively assessed all patients who had received a diagnosis of a rare genetic disorder after KTx. Results In our center, more than 30% (278/911) of kidney transplant (KTx) recipients were diagnosed with a causal nephropathy: Prevalence of rare genetic disorders in this group was 4.32% (12/278), including 2, 8‐dihydroxyadeninuria (2, 8‐DHA) disease (n = 2), HNF‐1B‐associated nephropathy (n = 2), UMOD‐related nephropathy (n = 5), Fabry disease (n = 1), INF2 focal segmental glomerulosclerosis (n = 1), and Senior‐Løken syndrome (n = 1). 2, 8‐DHA nephropathy relapsed in both patients causing an acute renal failure and jeopardizing the graft. Conclusions Kidney transplant recipients without a diagnosis of causal nephropathy appear to be a selected population in which rare genetic diseases might be more common than expected. As even a belated diagnosis after KTx can have a significant impact on graft and patient survival and on other family members, this possibility should be evaluated in KTx recipients without a known causal nephropathy.